The Industrial Organisation of the Dance Industry in the Netherlands: a Transaction Cost Perspective on Hybrid Forms of Organisation - Frank A.G. den Butter; Jelle Joustra (Tinbergen Institute, 2014)
The organization of Electronic Dance Music (EDM) events has become a major export product in the Netherlands. In order to respond quickly to the new trends and needs, innovative forms of cooperation between producers are to be set up for the organization of exciting new events. A case study on how these EDM events are actually organised in the Netherlands shows that the best way to do it is through hybrid forms of organisation, which combine horizontal forms of organisation through the market and vertical forms through the hierarchy. As EDM events are characterised by much asset specificity, the perspective of transaction cost economics indicates why this industry relies on hybrid forms of organisation. Trust between the collaborating partners, intrinsic motivation to be professional in the design and creation of new, ground-breaking music sensations and an extensiv e use of social media play a key role in lowering the transaction costs in the dance industry.
Keywords: D23; D85; E23; F60; L23; L24; L82; O31; P13; 330; Industrial organization; coordination costs; transaction cost economics; resource based view; cooperation in hybrid organizations; Electronic Dance Music (EDM) events; trust; use of social media